FOOD AND FEEDING HABITS OF SILVER POMFRET PAMPUS ARGENTEUS (EUPHRASEN) FROM BAY OF BENGAL WITH A NOTE ON ITS SIGNIFIICANCE IN FISHERY - Pati, S (Indian Journal of Fisheries, 2011)
A detailed study of the food and feedbg habits of siil